Potensi Pengembangan Industri dan Bioekonomi Berbasis Makanan Fermentasi Tradisional - Suyanto Pawiroharsono (JURNAL ILMU KEFARMASIAN INDONESIA, 2007)
Consumption of traditionally-fermented foods is around 25% of the total human food consumption. Indonesia has several important traditionally-fermented foods such as tempe (fermented soybean), tape (fermented cassava or glutinous rice), etc. Those foods are in general produced in smallscale industries or in home industries, which appear somewhat dirty, unhygienic and not standardized concerning its processing and the end product. The fermentation process benefits the improvement of its value: to preserve, to increase the nutrition value, flavor and taste as well as to produce a new product. Microorganisms play an important part in the fermentation process. The microorganisms involved in the traditionally-fermented food are usually a multiculture with a predominant strain. The microorganisms perform metabolic reactions and yield profit such as: (i) save to be consumed, (ii) easy to digest, and (iii) improving its nutritional and nutraceutical value, which are all advantageous for health. In addition, several traditionally-fermented foods also contain active substances potentially used for health, for preventing as well as for healing some diseases. The development of advanced biotechnology is to be expected in promoting the traditionally fermented food in favour of the food industry.